Anxiety and depression symptoms in young people with perinatally acquired HIV and HIV affected young people in England. Issue 8 (3rd August 2018) - Le Prevost, Marthe; Arenas-Pinto, Alejandro; Melvin, Diane; Parrott, Francesca; Foster, Caroline; Ford, Deborah; Evangeli, Michael; Winston, Alan; Sturgeon, Kate; Rowson, Katie; Gibb, Diana M.; Judd, Ali; et al.
ABSTRACT: Adolescents with perinatal HIV (PHIV) may be at higher risk of anxiety and depression than HIV negative young people. We investigated prevalence of anxiety and depression symptoms in 283 PHIV and 96 HIV-affected (HIV-negative) young people in England recruited into the Adolescents and Adults Living with Perinatal HIV (AALPHI) cohort. We used Hospital Anxiety and Depression Scale (HADS) scores and linear regression investigated predictors of higher (worse) scores.115 (41%) and 29 (30%) PHIV and HIV-affected young people were male, median age was 16 [interquartile range 15, 18] and 16 [14, 18] years and 241 (85%) and 71 (74%) were black African, respectively. There were no differences in anxiety and depression scores between PHIV and HIV-affected participants. Predictors of higher anxiety scores were a higher number of carers in childhood, speaking a language other than English at home, lower self-esteem, ever thinking life was not worth living and lower social functioning. Predictors of higher depression scores were male sex, death of one/both parents, school exclusion, lower self-esteem and lower social functioning. In conclusion, HIV status was not associated with anxiety or depression scores, but findings highlight the need to identify and support young people at higher risk of anxiety and depression.